Biomechanical parameters that may influence lower limb injury during landing in taekwondo - Ryu, S.; Lee, T.-K. (Medicina, 2021)
Background and Objectives: The jumping kick of Taekwondo was a unilateral exercise that repeatedly moves in one direction. The exercise was exposed to the risk of injury due to the heavy ground reaction force and load in the landing. The first purpose of this study was to compare the impact force (IF), peak vertical ground reaction force (PVGRF), vertical loading rate (VLR), vertical stiffness (VS), and landing foot angle (LFA) during the landing of the jumping kick according to the experience of lower injury. The second purpose of this study was to investigate the lower extremities` strength and the bilateral/ipsilateral asymmetry between the groups; Material and Methods: Ten injury-experience athletes (IG, age: 21.0 ± 0.8 years; height: 170.5 ± 4.1 cm; body weight: 66.7 ± 6.0 kg; career: 8.1 ± 5.0 years) and seven non-injury experience athletes (NG, age: 22.9 ± 4.0 years; height: 173.4 ± 3.1 cm; body weight: 67.9 ± 7.9 kg; career: 8.3 ± 5.0 years) participated; Results: There was no statistical difference between the two groups in the landing and lower extremity muscle strength impact variables. However, in the bilateral asymmetry of the ankle plantar flexor and the ipsilateral asymmetry of the hip abductor/adductor, IG was statistically larger than NG (p < 0.05). The landing foot angle also showed negative correlation to all impact variables (IF, PVGRF, VLR, and VS) (p < 0.05); Conclusions: It is desirable to place the landing foot down at a wide angle to prevent injury in performing Taekwondo jumping kicks. Although NGs have been shown to have better muscle strength symmetry and balance in some areas compared to IG, further research is needed to determine whether they are effective in preventing injury.